DEFINING BARRIERS IN TOURISM FOR PEOPLE WITH DISABILITIES IN UZBEKISTAN - Kuchkarova, Nigina Abduvaxob qizi (INTERNATIONAL CONFERENCES, 2023)
Today, travelers with impairments confront a lot of challenges in Uzbekistan. To begin with, these tourists feel uncomfortable due to social and cultural misunderstandings, accommodation problems, restricted data, and transportation problems. To investigate the questions, we used quantitative and qualitative methods; however, it should be admitted that the information on this topic was limited, especially on the Internet. The results were found by using small questionnaires on tourist websites and available statistics.